How the East Asian Crisis Will Change International Relations. (2nd July 2016) - Waldron, Arthur
Abstract : We may expect regional response to the tension and conflict in Asia begun by China in 2009 gradually to transform the international order in that region, where the United States has been the active great power. Today the United States is so overextended in commitments and so lacking in force structure (and political will) that she can no longer play that role. Nor, however, has China succeeded in her initial assumption that regional powers would defer to her vastly increased military power. Unless China finds a way to extricate herself, we may expect regional powers, each strengthening herself, to grow closer together as a group in which Tokyo plays an unaccustomed central role, both in diplomacy and arms supply, although in coordination with the United States. North Korea is also highly dangerous. The likely outcome is greater military strength generally, with South Korea and Japan nuclear powers.